Modal Analysis of Keropok Keping Drying Machine - Mohamad Syazwan Zafwan, Mohamad Suffian; Shahrol, Mohamaddan; Abg Mohd Aizuddin, Abg Mohd Mohtar (IOP Publishing, 2021)
This project is about analyzing the effect of vibration towards the keropok keping drying machine. The structure frame of the drying machine has been analyzed by conducting modal analysis using ANSYS software. The results of this project consist of the mode shape (pattern of vibration) with the respective natural frequency and the total deformation that occur at the component. The structure of the component is being analyzed whether they are going to resonate or not by comparing the natural frequency obtained from the analysis results and the operating speed of the drying machine. This study will benefit the small and medium-sized enterprise (SMEs), whom the machine was originally developed for, by giving a better performance and low maintenance cost thus minimize the production cost of keropok keping.